Inter-male aggression in relation to female availability and residence status in corn mice Calomys musculinus - Steinmann, Andrea Rosa (2011)
We conducted an experimental study to test the hypothesis that at low female availability males show intra-sexual aggressive behaviour and home range owners are more aggressive than home range intruders. Using field dyadic arena test we carried out 35 male-male trials in four 0.25 ha enclosures, two male-biased (experimental enclosures), and two unbiased (control enclosures). Dyadic encounters were conducted between un-related and sexually mature males of similar weight and age which established home ranges in the same enclosure at the same trapping session. Each inter-male encounter was performed in the home range of one of the opponents between the home range owner and a home range intruder. When sex ratios were male-biased, inter-male amicable behaviour was absent and we found significant rates of inter-male aggressiveness, being home range owners much more aggressive than intruders. In the unbiased enclosures inter-male encounters resulted mainly in non-interactive or amicable interactions.We found that inter-male aggression varied in relation to female availability being more evident in home range owners.